Precise robust adaptive dynamic surface control of permanent magnet synchronous motor based on extended state observer. Issue 5 (1st August 2017) - Li, Guotao; Xu, Wenfu; Zhao, Jianguo; Wang, Shuai; Li, Bing
Abstract : A novel precise position tracking controller is presented for permanent magnet synchronous motors (PMSMs). The proposed controller consisting of non‐linear extended state observer (ESO), tracking differentiator (TD) and dynamic surface control (DSC) can reject disturbance and can prevent PMSMs from chaos with parameters falling into some special areas. Compared with the conventional DSC approach, the TD of the proposed controller is designed to remove the explosion problem. Further, non‐linear ESO is designed to estimate the unmeasurable states and uncertainties of system, which together with TD significantly ameliorate the tracking performance and improve the disturbance rejection ability of system output in the presence of uncertainties and unmodelled dynamics of PMSMs. Different from the available control methods of PMSMs in reference, both the transient and steady‐state stability of the closed‐loop control system is proved by the Lyapunov method. Finally, comparative simulations are completed to demonstrate that the precise trajectory tracking performance, chaos‐suppressing performance and disturbance rejection performance of the proposed controller can be guaranteed.